2020
DOI: 10.1183/16000617.0106-2019
|View full text |Cite
|
Sign up to set email alerts
|

Defining a role for exercise training in the management of asthma

Abstract: The prevalence of asthma remains high worldwide, with increasing awareness of the morbidity and mortality from asthma in low-income countries. In the UK, despite the development of biological treatments, many patients remain suboptimally controlled, and mortality rates have been static for decades. Therefore, new approaches are needed to treat asthma that are scalable at minimal cost. Exercise immunology is an expanding field, and there is growing evidence that exercise can modulate inflammatory and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 80 publications
0
16
0
2
Order By: Relevance
“…Although some intervention studies of exercise as a diseasemodulating treatment have suggested clinical improvements for obese and non-obese patients with asthma, and exercise is encouraged in current treatment guidelines, there are no specific recommendations as to the intensity, frequency or duration of exercise exposure. This research is urgently needed so that more specific physical activity recommendations can be developed for children and adults with asthma [78][79][80].…”
Section: Asthma Controlmentioning
confidence: 99%
“…Although some intervention studies of exercise as a diseasemodulating treatment have suggested clinical improvements for obese and non-obese patients with asthma, and exercise is encouraged in current treatment guidelines, there are no specific recommendations as to the intensity, frequency or duration of exercise exposure. This research is urgently needed so that more specific physical activity recommendations can be developed for children and adults with asthma [78][79][80].…”
Section: Asthma Controlmentioning
confidence: 99%
“…Therefore, our results which show that a higher barrier to exercise correlates with a lower QoL score are not unexpected. Exercise is, however, known to improve health related QoL in asthma [4,23] and therefore interventions to address this paradox need investigating.…”
Section: Perceived Symptom Burden Impacts Perceived Barriers To Exercisementioning
confidence: 99%
“…Exercise is recommended in national and international guidelines for asthma management [1][2][3] and appears to have beneficial effects on symptom control, inflammation and lung function in patients with sub-optimally controlled asthma [4]. Despite this, physical activity levels in patients with severe asthma have been demonstrated to be impaired [5].…”
Section: Introductionmentioning
confidence: 99%
“…The increased amount of catecholamines, such as norepinephrine or epinephrine, in response to moderate-to-high-intensity exercise is well documented [ 1 , 3 ] and is likely to bind to β2-adrenergic receptors on the ILC2 cells, which would inhibit their activity. This promising result could further explain the known positive effects of aerobic exercise on reducing asthma symptoms [ 37 ]. We also found that CMV infection history was associated with dampened ILC mobilization following acute exercise in healthy young adults.…”
Section: Discussionmentioning
confidence: 92%